CRAC channel opening is determined by a series of Orai1 gating checkpoints in the transmembrane and cytosolic regions - Tiffner, Adéla; Schober, Romana; Höglinger, Carmen; Bonhenry, Daniel; Pandey, Saurabh; Lunz, Victoria; Sallinger, Matthias; Frischauf, Irene; Fahrner, Marc; Lindinger, Sonja; Maltan, Lena; Berlansky, Sascha; et al. (The Journal of biological chemistry, 2021)
The initial activation step in the gating of ubiquitously expressed Orai1 calcium (Ca2+) ion channels represents the activation of the Ca2+-sensor protein STIM1 upon Ca2+ store depletion of the endoplasmic reticulum. Previous studies using constitutively active Orai1 mutants gave rise to, but did not directly test, the hypothesis that STIM1-mediated Orai1 pore opening is accompanied by a global conformational change of all Orai transmembrane domain (TM) helices within the channel complex. We prove that a local conformational change spreads omnidirectionally within the Orai1 complex. Our results demonstrate that these locally induced global, opening-permissive TM motions are indispensable for pore opening and require clearance of a series of Orai1 gating checkpoints. We discovered these gating checkpoints in the middle and cytosolic extended TM domain regions. Our findings are based on a library of double point mutants that contain each one loss-of-function with one gain-of-function point mutation in a series of possible combinations. We demonstrated that an array of loss-of-function mutations are dominant over most gain-of-function mutations within the same as well as of an adjacent Orai subunit. We further identified inter- and intramolecular salt-bridge interactions of Orai subunits as a core element of an opening-permissive Orai channel architecture. Collectively, clearance and synergistic action of all these gating checkpoints are required to allow STIM1 coupling and Orai1 pore opening. Our results unravel novel insights in the preconditions of the unique fingerprint of CRAC channel activation, provide a valuable source for future structural resolutions, and help to understand the molecular basis of disease-causing mutations.
Keywords: Gene Expression Regulation; Protein Binding; nádorové proteiny; Ion Channel Gating; Patch-Clamp Techniques; protein ORAI1; Recombinant Proteins; Calcium; simulace molekulární dynamiky; mutace; konformace proteinů, beta-řetězec; vazebná místa; interakční proteinové domény a motivy; Bacterial Proteins; HEK293 buňky; Liposomes; Calcium Signaling; Phosphatidylcholines; Orai1; Electrophysiology; vápník; Stromal Interaction Molecule 1; Protein Conformation, beta-Strand; reportérové geny; gating iontového kanálu; AND-gate; Genetic Vectors; Molecular Dynamics Simulation; CRAC channel; HEK293 Cells; STIM1; metoda terčíkového zámku; konformace proteinů, alfa-helix; protein STIM1; Amino Acid Substitution; liposomy; luminescentní proteiny; rekombinantní proteiny; Protein Interaction Domains and Motifs; vazba proteinů; Binding Sites; Gating; zelené fluorescenční proteiny; vápníková signalizace; lidé; ORAI1 Protein; Humans; Protein Conformation, alpha-Helical; regulace genové exprese; substituce aminokyselin; Opening-permissive conformation; bakteriální proteiny; Green Fluorescent Proteins; Neoplasm Proteins; Signal propagation; Luminescent Proteins; genetické vektory; fosfatidylcholiny; Mutation; Gating checkpoints; Genes, Reporter